Prefrontal cortex reactivity underlies trait vulnerability to chronic social defeat stress - Kumar, Sunil (2014)
Psychological stress contributes to the onset and exacerbation of nearly all neuropsychiatric disorders. Individual differences in stress-regulatory circuits can therefore dramatically affect vulnerability to these illnesses. Here we identify neural circuit mechanisms underlying individual differences in vulnerability to stress using a murine model of chronic social defeat stress. In chronically stressed mice, we find that the degree of prefrontal cortex (PFC) control of amygdala activity predicts stress-susceptibility in individual mice. Critically, we also find that individual differences in PFC activation (i.e. reactivity) during exposure to an aggressor mouse predict the emergence stress-induced behavioral deficits in stress naïve mice. Finally, we show that naturally occurring differences in PFC reactivity directly correspond to the intrinsic firing rate of PFC neurons. This demonstrates that naturally occurring differences in PFC function underlie individual differences in vulnerability to stress, raising the hypothesis that PFC modulation may prevent stress-induced psychiatric disorders.